Influence Of Library Environment And User Education On Undergraduates’ Use Of Library At The University Of Ibadan, Nigeria - Oluyomı Folorunso; Esther Njoku (European Scientific Journal, ESJ, 2016)
The study investigated the influence of library environment and user education on undergraduates’ use of the University central library at the University of Ibadan, Nigeria.The study adopted the survey research design and the population consisted of 18,034 regular undergraduates in ten faculties from which a sample size of 360 respondents was selected using the proportionate, random sampling technique. The research instrument used for data collection was a self-developed questionnaire while data was analysed using frequency distribution, percentages, mean and standard deviation together with regression and correlation analysis.The finding of the study revealed that library environment at the University of Ibadan was characterised by good library building (mean=3.75), seating arrangement (mean=3.59), availability of information resources (mean=3.54), and fair electricity supply while there was poor Internet connectivity and Wi-Fi within and outside the library (mean=2.39). Methods of delivering user education were library orientation for new students (64.3%) and use of library course (53.4%) with guided library tour. Most undergraduates used the library daily or weekly in order to study and read for examinations. However, inadequate technological facilities to use for electronic sources (mean=2.65), and poor network/internet connectivity to access electronic databases were some of the major challenges of using the University library. The study found a significant relationship between the independent variables (library environment and user education) and the dependent variable (use of library) (r = .342, N= 322, P < .01); while both library environment and user education jointly and independently contributed to the use of library among the undergraduates. programmes given more priority in the University library in order to sensitise more students and draw their attention to the available resources and services while the environment of the University library (both internal and external) should be made more conducive to always attract the users to the library.